Event‐Scale Dynamics of a Parabolic Dune and Its Relevance for Mesoscale Evolution. Issue 11 (27th November 2018) - Delgado‐Fernandez, Irene; Smyth, Thomas A. G.; Jackson, Derek W. T.; Smith, Alexander B.; Davidson‐Arnott, Robin G. D.
Abstract: Parabolic dunes are widespread aeolian landforms found in a variety of environments. Despite modeling advances and good understanding of how they evolve, there is limited empirical data on their dynamics at short time scales of hours and on how these dynamics relate to their medium‐term evolution. This study presents the most comprehensive data set to date on aeolian processes (airflow and sediment transport) inside a parabolic dune at an event scale. This is coupled with information on elevation changes inside the landform to understand its morphological response to a single wind event. Results are contextualized against the medium‐term (years) allowing us to investigate one of the most persistent conundrums in geomorphology, that of the significance of short‐term findings for landform evolution. Our field data suggested three key findings: (1) sediment transport rates inside parabolic dunes correlate well with wind speeds rather than turbulence; (2) up to several tonnes of sand can move through these landforms in a few hours; and (3) short‐term elevation changes inside parabolic dunes can be complex and different from long‐term net spatial patterns, including simultaneous erosion and accumulation along the same wall. Modeled airflow patterns along the basin were similar to those measured in situ for a range of common wind directions, demonstrating the potential for strong transport during multiple events. Mesoscale analyses suggested that the measured event was representative of the type of events potentially driving significant geomorphic changes over years, with supply‐limiting conditions playing an important role in resultant flux amounts. Plain Language Summary: We examine detailed surface changes inside a parabolic dune feature during a wind event. Resulting accelerated winds gave very strong transport rates, correlating well with average wind speed measurements across the landform basin. Elevation changes as a result of the event were up to ±0.3 m in places, with complex surface patterns previously not observed including deposition against the upper slopes of the erosional walls. We estimate that a total of approximately 4.8 tonnes moved through this dynamic landform feature in 3.5 hr. The contextualization of the event in a time scale of 2 years showed that this was a common type of event, with an average frequency of almost three times per month and of average magnitude. This suggests that similar events should be able to move similar amounts of sand, hence making these landforms very dynamic and responsive to wind events. Key Points: First empirical study linking strong aeolian transport (approximately 5 tonnes) during a wind event with 3‐D complex surface responses inside a parabolic dune Airflow modeling predicted similar airflow dynamics (and therefore potential sediment transport) along the basin for a range of characteristic wind directions Mesoscale contextualization revealed that short‐term data were collected during a common type of event and were therefore significant for landform evolution